X - McDowall, Alistair; McDowall, Alistair (Bloomsbury Publishing, 2018)
Billions of miles from home, the lone research base on Pluto has lost contact with Earth. Unable to leave or send for help, the skeleton crew sit waiting. Waiting. Waiting long enough for time to start eating away at them. To lose all sense of it. To start seeing things in the dark outside.